Analysis of Genetic Damage in Lymphocytes of Former Uranium Processing Workers - Zölzer, Friedo; Havránková, Renata; Freitinger Skalická, Zuzana; Rössnerová, Andrea; Šrám, Radím (Karger, 2015)
The frequency of cells containing micronuclei (MN) and the presence of centromeres in these MN were analysed in lymphocytes of 98 men from Southern Bohemia. 46 of them had worked at the uranium processing plant, “MAPE Mydlovary”, which has been defunct since 1991; 52 men were controls from the same area. Fluorescence in situ hybridization (FISH) method using Human Pan Centromeric Chromosome Paint was employed to recognize centromere positive (CEN+) and negative (CEN-) micronuclei. A total of 1000 binucleate cells (BNC) per participant were analysed after cytochalasin B treatment. All BNC with MN (centromere positive or negative) were recorded by the ISIS software (MetaSystems). No differences were found between formerly exposed workers and the control group, neither in the total frequency of cells with MN per 1000 BNC (mean levels ± standard deviation were 9.1±3.1 and 9.8±2.5, resp.), nor in the percentage of CEN- among all MN was nearly equal for both groups (50±18 and 49±17, resp.). Also, there was no difference between individuals living in the three villages closest to the uranium processing plant and those living further away (9.1±3.0 and 9.6±2.8, resp., for the frequency of cells with MN per 1000 BNC and 50±20 and 50±17, resp., for the percentage of CEN- among all MN). Considering the fact that effective doses of the workers at MAPE Mydlovary were overall similar to those of former uranium miners (in an earlier study) with whom higher frequencies of centromere negative MN have been found more than 10 years after they had finished work underground, these results are somewhat surprising. A more detailed analysis of the exposures indicates that uranium miners received a greater percentage of their effective dose from the inhalation of radon and its daughters, whereas uranium processing workers received it from the incorporation of long-lived radioactive nuclides such as uranium.
Keywords: Alpha radiation; Genomic instability; Micronucleus-centromere test; Radon; Uranium miners